Analisis Semiotika Roland Barthes pada Arsitektur Masjid Agung Sultan Thaf Sinar Basarsyah di Lubuk Pakam - Alifia Zahra Shafira; Fatimatuzzahra Nasution; Yenny Haidar Naburju; Rizqa Karima; Isfira Ainy (Jurnal Kajian dan Penelitian Umum, 2024)
This research examines the meaning of architecture and ornaments in the Sultan Thaf Sinar Basarsyah Grand Mosque in Lubuk Pakam, Deli Serdang using Roland Barthes' semiotic approach. Using a qualitative research method, this study analyzes the denotation, connotation, and mythical meanings of various architectural elements of the mosque such as building form, interior space, color, and ornaments such as windows, mihrab, doors, calligraphy, and drum. The results show that the design of this mosque combines elements of local culture from three tribes (Karo, Simalungun, and Malay) with typical Middle Eastern ornaments. The unique shape of the dome depicts the hijaiyah letters that form the lafaz Allah, while the choice of colors and ornaments reflects the effort to unite the diversity of local cultures. The mosque, which was built on an area of 16,307 square meters, not only functions as a place of worship but also as a center of Muslim activities that spread the values of brotherhood, love, unity and harmony.